2022
DOI: 10.1002/pc.26795
|View full text |Cite
|
Sign up to set email alerts
|

A review on performance of near‐surface mounted‐carbon fiber‐reinforced polymer laminates bonded into slits

Abstract: The near‐surface mounted (NSM) technique over the years has become the most popular retrofitting technique for obtaining enhanced strength and durability in reinforced concrete structural elements. It is mostly preferred for its easy application of composites in grooves cut on specimen concrete cover. The specimen surface is prepared with slits where polymer composite laminates are placed along with adhesives as filler to attain good bonding between laminates and the surface. The paper reviews the NSM carbon f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 150 publications
0
4
0
Order By: Relevance
“…Even slight perfection in the fabrication process can improve the laminate strength for a particular loading category. [ 29–32 ] Hence, the prediction accuracy of Anisomorphic CLD can vary with the fabrication technique and cannot be employed straight away for any random laminate or stacking sequence. Anisomorphic CLDs can be used after experimental cross‐verification as it saves enormous money and effort behind a reliable life envelope prediction.…”
Section: Resultsmentioning
confidence: 99%
“…Even slight perfection in the fabrication process can improve the laminate strength for a particular loading category. [ 29–32 ] Hence, the prediction accuracy of Anisomorphic CLD can vary with the fabrication technique and cannot be employed straight away for any random laminate or stacking sequence. Anisomorphic CLDs can be used after experimental cross‐verification as it saves enormous money and effort behind a reliable life envelope prediction.…”
Section: Resultsmentioning
confidence: 99%
“…The total shielding effectiveness is calculated using Equation (4). Figures 5 and 6 depict the SE of the carbon fiber/epoxy composite sample (S0) in X-band (8)(9)(10)(11)(12) and Ku-band (12-18 GHz) with different orientations of carbon fiber as shown in Figure 1B. It has been observed that without of zirconia nanofiller grading the shielding is increased significantly with orientation both in the X-band and Ku-band shown in Figures 5 and 6.…”
Section: Shielding Effectiveness Studymentioning
confidence: 94%
“…[6] Research on polymer-based composites has increased tremendously due to their exclusive properties such as being lightweight, flexible, resistant to corrosion, and moldability with higher surface area for reflection and multiple reflections. [7][8][9][10] The carbon fiber-reinforced composite (CFRC) effectively replaces aluminum and titanium alloys due to their superior mechanical strength. [11] Besides its mechanical properties, CFRC contributes to EMI shielding.…”
Section: Introductionmentioning
confidence: 99%
“…Polymer composites have exclusive properties like being resistant to corrosion, flexible, lightweight, and moldability. [6][7][8][9] The epoxy polymer has excellent mechanical properties, heat resistance, and adhesion. But, the epoxy polymer is brittle.…”
Section: Introductionmentioning
confidence: 99%